Contrasting perspectives – practitioner's viewpoint on personalised marketing communication. (8th April 2019) - Strycharz, Joanna; van Noort, Guda; Helberger, Natali; Smit, Edith
Abstract : Purpose: The purpose of this paper is to provide insights into personalisation from a practitioner's perspective to bridge the practitioner-academia gap and steer the research agenda. A wide scope of research has investigated personalisation from a consumer perspective. The current study aims at bridging the consumer and practitioner perspective by entering into a dialogue about the practical application of personalisation. It takes the personalisation process model by Vesanen and Raulas (2006) as the starting point. Design/methodology/approach: Lead by the exploratory character of the study, semi-structured expert interviews were conducted with marketers, market researchers and online privacy specialists. Findings: The results showcase how practitioners view the issues present in consumer research. First, they are overly positive about personalisation. Second, they are aware of constraining factors; findings showcase best practices to mitigate them. Finally, practitioners are aware of controversies surrounding personalisation and thus engage in ethical discussions on personalisation. Research limitations/implications: This study shows that practitioners have somewhat different believes about the utility and appreciation of personalised marketing practices than consumers. It also shows awareness of some of the key concerns of consumers, and that such awareness translates into organisational and technological solutions that can even go beyond what is currently mandated by law. Six insights into personalised marketing as well as expectations for the future of the phenomenon are discussed to steer the research agenda. Practical implications: Insights into the practice of personalisation contribute to a shared understanding of this phenomenon between involved actors, such as marketers, advertisers, and consumer representatives. In addition, implications for lawmakers are discussed, suggesting that the implementation of privacy laws needs more clarity and that actions aiming at improving consumer knowledge are needed. Originality/value: The paper contributes to the literature first, by drafting a descriptive map of personalisation from a practitioners' perspective and contrasting it with the perspective stemming from consumer research and, second, by offering insights into the current developments and direct implications for practice and future research.